2013
DOI: 10.3233/jpd-120165
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Impulse Control Disorders in Parkinson's Disease

Abstract: Throughout the past decade it has been recognized that dopaminergic medication administered to remedy motor symptoms in Parkinson's disease is associated with an enhanced risk for impulse control disorders and related compulsive behaviors such as hobbyism, punding, and the dopamine dysregulation syndrome. These complications are relatively frequent, affecting 6-15.5% of patients, and they most often appear, or worsen, after initiation of dopaminergic therapy or dosage increase. Recently, impulse control disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 223 publications
5
60
0
5
Order By: Relevance
“…For PD patients, initial cross-sectional studies that used formal assessments of ICDs reported an estimated prevalence of 1.7% to 7.0% for compulsive gambling, 3.5% for CSB, 27 and 0.4% to 3.0% for compulsive buying. [28][29][30][31] Compulsive or binge eating was also reported in PD, but its prevalence was not initially reported.…”
Section: Frequencymentioning
confidence: 99%
“…For PD patients, initial cross-sectional studies that used formal assessments of ICDs reported an estimated prevalence of 1.7% to 7.0% for compulsive gambling, 3.5% for CSB, 27 and 0.4% to 3.0% for compulsive buying. [28][29][30][31] Compulsive or binge eating was also reported in PD, but its prevalence was not initially reported.…”
Section: Frequencymentioning
confidence: 99%
“…Deep brain stimulation is an effective treatment for several neurological diseases and conditions, including Parkinson’s disease and depression (Mayberg, 2009; Callesen et al, 2013). In rodent studies, electrical stimulation of the LHb reduced cocaine cravings, self-administration, and reinstatement while improving extinction.…”
Section: Electrical Stimulation In the Lateral Habenula Reduces Cocaimentioning
confidence: 99%
“…A recent study found that patients with ICDs were more likely to be on antidepressant medications and had more motor complications than those without ICDs (Mack et al, 2013). In addition to dopaminergic medications, studies also show that ICDs can be caused by deep brain stimulation of the subthalamic nucleus (Frank et al, 2007; Callesen et al, 2013a; but also see Santangelo et al, 2013). Studies also show that cognitive behavioral therapy can ameliorate ICDs in PD patients (Okai et al, 2013).…”
Section: Impulse Control Disorders In Pdmentioning
confidence: 99%